The Rahab Story in Josephus - Begg, C. (Liber Annuus, 2005)
Abstract Three questions have been studied in my essay. The first of those questions asked about the text-form(s) of Joshua 2 utilized by Josephus. My second opening question concerned Josephusʼ rewriting techniques in his Rahab story. Of these, the most conspicuous are probably his re-arrangements. Such re-arrangements affect both his placement of the Rahab-episode within its context. Likewise notable are Josephusʼ compressions and omissions of source material. At the same time, Josephus also adds to/expatiates on the Bibleʼs Rahab-account. A final category of Josephusʼ re-writing techniques comprises his modifications of the Bibleʼs presentation. What differences - I further asked in my second opening question between the biblical and Josephan Rahab-stories result from the historianʼs application of the above re-writing techniques? In my third opening question, I asked about the possible affinities between Josephusʼ version of the Rahab-story and the commentaries on it elsewhere in ancient Jewish and Christian tradition.